2019
DOI: 10.1111/pan.13712
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of clonidine on postoperative vomiting and pain in pediatric ophthalmic surgery: A systematic review and meta‐analysis

Abstract: Background Postoperative vomiting and pain are common, unpleasant phenomena in pediatric patients undergoing ophthalmic surgery. Clonidine has antiemetic and analgesic properties and thus may be used as premedication to reduce postoperative vomiting and pain. Aim To assess whether clonidine premedication may safely decrease postoperative vomiting and postoperative pain in pediatric patients who received an ophthalmic surgery. Methods We systematically searched PubMed, EMBASE, Cochrane Library, and Scopus datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Our current findings suggested that dexmedetomidine reduces the number of patients requiring analgesia and the pain intensity among children undergoing strabismus surgery. This result is consistent with those of previous studies [36]. Therefore, our results may be crucial for updating clinical practice guidelines in the future.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…Our current findings suggested that dexmedetomidine reduces the number of patients requiring analgesia and the pain intensity among children undergoing strabismus surgery. This result is consistent with those of previous studies [36]. Therefore, our results may be crucial for updating clinical practice guidelines in the future.…”
Section: Plos Onesupporting
confidence: 93%
“…In a 2016 guideline, ondansetron combined with dexamethasone-but not dexmedetomidine alonewas recommended to increase the effectiveness of PONV prevention in children scheduled for strabismus surgery [39]. In a 2019 meta-analysis [36], compared with placebo use, premedication with clonidine (another α2 agonist) decreased PONV incidence by 17% in children undergoing strabismus surgery, which is in agreement with our findings. Moreover, for PONV incidence, we found 0% heterogeneity and narrow CIs for its RR.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…The 20 studies were published across a 15-year period (1995–2020) and from 10 different countries: the USA (n=6),12 21 22 25 28 29 Taiwan (n=3),11 13 20 Australia (n=2),14 24 China (n=2),15 27 Germany (n=2),18 19 Belgium (n=1),30 Japan (n=1),16 Brazil (n=1),17 the UK (n=1)23 and India (n=1)26 (tables 1 and 2). Out of 20 eligible studies, only 7 studies included information about funding sources 11 16 18 19 23 24 29.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that systemic clonidine is effective in reducing acute postoperative pain and that systemic clonidine can also be helpful in reducing chronic pain. [ 13 14 ] For better control of renal colic, a combination of two drugs can be used instead of one. So far, several studies have been performed to evaluate the effect of opioids alone or in combination with another drug, as well as the effect of systemic clonidine in reducing pain.…”
Section: Introductionmentioning
confidence: 99%